2020
DOI: 10.1037/vio0000233
|View full text |Cite
|
Sign up to set email alerts
|

Nonconsensual pornography among U.S. adults: A sexual scripts framework on victimization, perpetration, and health correlates for women and men.

Abstract: This study examines rates of nonconsensual pornography victimization and perpetration in the United States, as well as health correlates of victimization. Nonconsensual pornography (aka "revenge porn") is defined as the distribution of sexually explicit images without consent, and is a growing form of image-based sexual abuse. In this study, we assessed rates of nonconsensual pornography victimization and perpetration among online U.S. adults using an inclusive definition of nonconsensual pornography (i.e., di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
117
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(141 citation statements)
references
References 62 publications
(82 reference statements)
9
117
3
Order By: Relevance
“…Furthermore, Henry, Flynn, and Powell (2019) found that men are signifi cantly more likely to have perpetrated any form of image-based sexual abuse compared to women, while Clancy, Klettke, and Hallford (2019) Article: Homosocial positionings and ambivalent participation Morten Birk Hansen Mandau found that males are more likely to endorse improved social status as a reason for nonconsensually sharing sexual images (40.7 percent) than are females (5 percent). Ruvalcaba and Eaton (2019) found that women are signifi cantly more likely to be victims of the non-consensual sharing of private sexual images than men, who in turn are signifi cantly more likely to be perpetrators of this behaviour. Female victims also reported signifi cantly lower mental well-being and higher levels of somatic symptoms compared to non-victims, while no signifi cant diff erences were found between male victims and non-victims.…”
Section: Gendered Aspects Of the Non-consensual Sharing Of Sexual Imagesmentioning
confidence: 95%
See 4 more Smart Citations
“…Furthermore, Henry, Flynn, and Powell (2019) found that men are signifi cantly more likely to have perpetrated any form of image-based sexual abuse compared to women, while Clancy, Klettke, and Hallford (2019) Article: Homosocial positionings and ambivalent participation Morten Birk Hansen Mandau found that males are more likely to endorse improved social status as a reason for nonconsensually sharing sexual images (40.7 percent) than are females (5 percent). Ruvalcaba and Eaton (2019) found that women are signifi cantly more likely to be victims of the non-consensual sharing of private sexual images than men, who in turn are signifi cantly more likely to be perpetrators of this behaviour. Female victims also reported signifi cantly lower mental well-being and higher levels of somatic symptoms compared to non-victims, while no signifi cant diff erences were found between male victims and non-victims.…”
Section: Gendered Aspects Of the Non-consensual Sharing Of Sexual Imagesmentioning
confidence: 95%
“…Female victims also reported signifi cantly lower mental well-being and higher levels of somatic symptoms compared to non-victims, while no signifi cant diff erences were found between male victims and non-victims. Ruvalcaba and Eaton (2019) interpret this diff erence as being related to the sexual double standard (Bordini & Sperb, 2013), according to which females are punished and stigmatized for expressing their sexuality, while males are not punished, but instead rewarded for actively displaying their sexuality. Sexual double standards have been described in several studies on youth sexting (Lippman & Campbell, 2014;Ricciardelli & Adorjan, 2019;Ringrose, Harvey, Gill, & Livingstone, 2013) and have been linked to the phenomenon of "slut-shaming", commonly defi ned as "the act of attacking a female for perceived or real sexual activity by calling her a slut or similar names" (Van Royen, Poels, Vandebosch, & Walrave, 2018, p. 82).…”
Section: Gendered Aspects Of the Non-consensual Sharing Of Sexual Imagesmentioning
confidence: 99%
See 3 more Smart Citations